PROMOTING OPEN GOVERNMENT PARTNERSHIP: INSIGHTS FROM ARGENTINA'S BUENOS AIRES - Afandi, Syed Agung; Erdayani, Rizki; Afandi, Muslim (Polteknik Imigrasi, 2025)
This study aims to analyze the open government of Buenos Aires, Argentina. Buenos Aires plays a leading role as the only pilot local government program of the Open Government Partnership in the country. Qualitative approaches and bibliometric analysis methods are used in this study. The research data were obtained from the official website of the Buenos Aires government and sourced from the Google Scholar database. The findings of this study indicate that the open government of Buenos Aires is not popular. The dominant issues include transparency, accountability, public trust, COVID-19, participation, collaboration, e-government, governance, smart cities, and disputes. Current issues include healthcare centers, information, data, the environment, digital platforms, and civil technology. Buenos Aires is currently focusing on three of its open government commitments, including the participation of children and adolescents as subjects of rights in the design of public policies; urban woodland management in the City of Buenos Aires through the open government perspective; plain language: a tool to guarantee simple, fast and effective communication between the state and citizens. These commitments have the potential to create a more open government in Buenos Aires. The findings of this study serve as recommendations for decision-makers in Buenos Aires, as well as for all local governments in Argentina and all members of the Open Government Partnership in implementing open government.